Tracking Identity Politics in the 2019 Presidential Election Campaign (Framing Analysis of the 2019 Presidential Election Campaign) - Harsen Roy Tampomuri; Yuni Murni Tampomuri (Novateur Publications, 2022)
The dynamics of national politics in the 2019 Presidential election (Pilpres) attracted the attention of political scientists, including the wider community. The 2019 presidential election brought together Joko Widodo and Prabowo Subianto in a fierce contest. The issue of image politics but also the politicization of identity (identity politics) is unstoppable among the people who are also encouraged by media framing. Political figures often carry out identity politicization to increase electability. The information medium, which is expected to be independent, is actually trapped in the vortex of identity politics ahead of the general election. In fact, the political affiliations of media owners also influence various reports. This study was conducted to track and analyze various framings carried out through mass media coverage in the 2019 Presidential Election. A qualitative approach with secondary data and framing analysis from Robert N. Entman was used. The results of the study show that there is a political framing of imagery and even identity politics in mass media coverage of the 2019 presidential election campaign.
Keywords: Framing Media, Politik Pencitraan, Politik Identitas, Pilpres 2019